2007
DOI: 10.1289/ehp.9994
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Early Childhood Blood Lead Levels and Performance on End-of-Grade Tests

Abstract: BackgroundChildhood lead poisoning remains a critical environmental health concern. Low-level lead exposure has been linked to decreased performance on standardized IQ tests for school-aged children.ObjectiveIn this study we sought to determine whether blood lead levels in early childhood are related to educational achievement in early elementary school as measured by performance on end-of-grade (EOG) testing.MethodsEducational testing data for 4th-grade students from the 2000–2004 North Carolina Education Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
106
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(120 citation statements)
references
References 16 publications
4
106
0
4
Order By: Relevance
“…2 Historical and recent research show that there is no safe exposure to lead in children without doing permanent and irreparable neurological, neurobehavioral, and physiological damage. [2][3][4][5][6][7][8][9][10][11][12][13] This damage may include a wide range of problems in children with the most common effect being permanent behavioral and learning deficits such as reduced IQ, ADHD, memory loss, etc. 2 Evidence of this irreparable damage led the Centers for Disease Control and Prevention (CDC) to lower the reference level (previously called the level of concern) for lead poisoning from ≥10 to ≥5 μg/dL in 2012.…”
Section: Introductionmentioning
confidence: 99%
“…2 Historical and recent research show that there is no safe exposure to lead in children without doing permanent and irreparable neurological, neurobehavioral, and physiological damage. [2][3][4][5][6][7][8][9][10][11][12][13] This damage may include a wide range of problems in children with the most common effect being permanent behavioral and learning deficits such as reduced IQ, ADHD, memory loss, etc. 2 Evidence of this irreparable damage led the Centers for Disease Control and Prevention (CDC) to lower the reference level (previously called the level of concern) for lead poisoning from ≥10 to ≥5 μg/dL in 2012.…”
Section: Introductionmentioning
confidence: 99%
“…A number of epidemiologic studies done since the 1980s have revealed that Pb impairs normal development of cognitive functions of children [1]. Exposure to Pb has been related to lower intelligence quotient (IQ) [2], poor academic achievement [3], and delinquent behavior [4]. Moreover, concern has recently been raised that adverse effects are seen at exposure levels lower than were considered safe in the past [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…(Byers & Lord, 1943;Marlowe, 1995;David et al, 1976; The negative correlation between blood lead and SAT trends is consistent with research demonstrating an inverse relationship between preschool blood lead and IQ, and research showing IQ is an excellent predictor of academic achievement. (Schwartz, 1994; U.S. Centers for Disease Control and Prevention, 1991;Lanphear et al 2005;Miranda et. al, 2007;Canfield et al, 2003;Neisser et.…”
Section: Correlation and Causation Conclusionmentioning
confidence: 99%
“…Many studies also show an inverse relationship between blood lead and IQ and academic achievement (U.S. Centers for Disease Control and Prevention, 1991;Lanphear et al 2005;Miranda et. al, 2007).…”
Section: Introductionmentioning
confidence: 99%